Titel prent: De soc. dem. stemmen tegen de oorlogsbegroting : de Arbeid: Jij ben me nog altijd te leelijk - Hahn, Albert,
Titel prent: De soc. dem. stemmen tegen de oorlogsbegroting : de Arbeid: Jij ben me nog altijd te leelijk.